Students' Perception On The Use Of Youtube In English Language Learning At Eleventh Grade Of Sma Dwijendra Bualu - Abul, Wihelmina Antriana; Sintadewi, Ni Made Dita; Suryantini, Made Detri (Peneliti.net, 2025)
This study aims to determine the perception of eleventh grade students of Dwijendra Bualu High School towards the use of YouTube as an English learning media. The background of this study is based on the rapid development of digital technology, where YouTube is one of the platforms that are widely accessed by students. This study used a descriptive qualitative approach with data collection techniques through questionnaires and semi-structured interviews. The research subjects were grade XI students who had used YouTube as part of the English learning process. The results show that the majority of students have a positive perception of the use of YouTube in English learning. They consider YouTube can improve vocabulary understanding, pronunciation, and listening skills in a more interesting and interactive way than conventional methods. However, some students also stated that the use of YouTube needs to be well directed so as not to cause distraction or inappropriate use. Overall, YouTube is perceived as an effective and relevant tool in supporting English language learning in the digital era.